User satisfaction with the structure and content of the NEXit intervention, a text messaging-based smoking cessation programme - Müssener, Ulrika (BMC Public Health, 2016)
BACKGROUND: Smoking is still the leading cause of preventable ill health and death. There is a limited amount of evidence for effective smoking cessation interventions among young people. To address this, a text messaging-based smoking cessation programme, the NEXit intervention, was developed. Short-term effectiveness, measured immediately after the 12-week intervention revealed that 26% of smokers in the intervention group had prolonged abstinence compared with 15% in the control group. The present study was performed to explore the users’ experiences of the structure and content of the intervention in order to further develop the intervention. METHODS: Students participating in the main NEXit randomized controlled trial were invited to grade their experiences of the structure and content of the intervention after having completed follow-up. The participants received an e-mail with an electronic link to a short questionnaire. Descriptive analysis of the distribution of the responses to the questionnaire was performed. Free-text comments to 14 questions were analysed. RESULTS: The response rate for the user feedback questionnaire was 35% (n = 289/827) and 428 free-text comments were collected. The first motivational phase of the intervention was appreciated by 55% (158/289) of the participants. Most participants wanted to quit smoking immediately and only 124/289 (43%) agreed to have to decide a quit-date in the future. Most participants 199/289 (69%) found the content of the messages in the core programme to be very good or good, and the variability between content types was appreciated by 78% (224/289). Only 34% (97/289) of the participants thought that all or nearly all messages were valuable, and some mentioned that it was not really the content that mattered, but that the messages served as a reminder about the decision to quit smoking. CONCLUSIONS: The programme was largely perceived satisfactory in most aspects concerning structure and content by young people and most participants stated that they would recommend it to a friend who wants to quit smoking. The motivational phase might be worth shortening and the number of messages around the quit date itself reduced. Shorter messages seemed to be more acceptable. TRIAL REGISTRATION: ISRCTN75766527. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12889-016-3848-5) contains supplementary material, which is available to authorized users.